Microarray profile of circular RNAs identifies CBT15_circR_28491 and T helper cells as new regulators for deep vein thrombosis - Chen, Weiwei; Zhu, Ying; Niu, Sihua; Zhou, Yan; Chang, Jian; Gan, Shujie (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDeep vein thrombosis (DVT) is the third most common cardiovascular disorder and can lead to high mortality and morbidity. This study aimed to clarify the molecular and immune characteristics of circular RNAs (circRNAs) and messenger RNAs (mRNAs) in DVT progression.MethodsDVT-associated dataset GSE148333 was downloaded to screen differentially expressed circRNAs and mRNAs using the limma package. DVT-related modules/genes were then filtered using WGCNA. Subsequently, key hub genes associated with DVT were determined using four algorithms: MCC, MNC, EPC, and DEGREE. A circRNA–miRNA–hub gene network was then constructed, and the relationship between the DVT-related hub genes and immunity was analyzed. Finally, a DVT rat model was established to verify the expression of critical circRNAs and hub genes using real-time quantitative PCR.ResultsA total of 421 circRNAs and 1,082 mRNAs were differentially expressed in DVT. Among these, 235 circRNAs and 207 mRNAs were identified as DVT-related and were significantly enriched in signaling pathways including NOD-like receptor, mTOR, FoxO, p53, and cell cycle. Thereafter, 17 important hub genes were obtained, including Birc5, Plk4, Dlgap5, Spag5, Cdca2, Ccnb1, Cdca8, Kif18a, Kif2c, Espl1, Cenpu, Cdc20, Ncapg, Asf1b, Nek2, Aurkb, and Cenpw. Subsequently, 227 circRNA–miRNA pairs and 84 miRNA–hub gene pairs were included to construct a circRNA–miRNA–hub gene network, containing CBT15_circR_28491-rno-miR-139-3p-Kif18a/Cdca8/Nek2. Eight immune cell types showed differential infiltration levels in DVT and controls, with T helper cells positively related with all 17 hub genes.ConclusionsThis study offers valuable information about circRNAs and mRNAs in DVT, identifying CBT15_circR_28491-rno-miR-139-3p-Kif18a/Cdca8/Nek2 as a potential target for DVT management.